Upregulation of Mir342 in Diet-Induced Obesity Mouse and the Hypothalamic Appetite Control - Zhang, Dongxiao; Yamaguchi, Satoshi; Zhang, Xinhao; Yang, Boxuan; Kurooka, Naoko; Sugawara, Ryosuke; Albuayjan, Haya Hamed H.; Nakatsuka, Atsuko; Eguchi, Jun; Hiyama, Takeshi Y.; Kamiya, Atsunori; Wada, Jun (Frontiers in Endocrinology, 2021)
In obesity and type 2 diabetes, numerous genes are differentially expressed, and microRNAs are involved in transcriptional regulation of target mRNAs, but miRNAs critically involved in the appetite control are not known. Here, we identified upregulation of miR-342-3p and its host gene Evl in brain and adipose tissues in C57BL/6 mice fed with high fat-high sucrose (HFHS) chow by RNA sequencing. Mir342 (-/-) mice fed with HFHS chow were protected from obesity and diabetes. The hypothalamic arcuate nucleus neurons co-express Mir342 and EVL. The percentage of activated NPY+pSTAT3+ neurons were reduced, while POMC+pSTAT3+ neurons increased in Mir342 (-/-) mice and they demonstrated the reduction of food intake and amelioration of metabolic phenotypes. Snap25 was identified as a major target gene of miR-342-3p and the reduced expression of Snap25 may link to functional impairment hypothalamic neurons and excess of food intake. The inhibition of miR-342-3p may be a potential candidate for miRNA-based therapy.